The effectiveness of treaters against sucking pests in winter wheat agrocenosis - Grytsiuk , N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. The assesment of the technological and economic efficiency of the insecticidal treaters of different chemical groups against autumn pests entomocomplex.Methods. Standard entomological methods were used to determine the number of insect pests in winter wheat agrocenosis. The leafhoppers and Schizaphis graminum count was carried out during autumn period (phase ВВСН 21—30) on the 7th, 14th day after germination. The leafhoppers were counted by using the method of accounting plots, and the Schizaphis graminum were counted by using the method of plant tests.Results. The phytophagous insects control by means of plant protection products is an effective method, but the result depends on the choice of the insecticides among a wide range of preparations. The results of the effects of treating on the dynamics of leafhoppers and Schizaphis graminum count in winter wheat agrocenosis have been presented. Entomological monitoring of the wheat field in the minds of the first-last-last field established that the biggest threat to winter wheat crops was cicadas and grasshoppers. The results of studying of modern insecticidal disinfactants against sucking pest density in a phase of ВВСН 21—30 have been presented.Conclusions. It has been established that the preparations Gaucho Plus 466 FS, TH, 0.5 l/t, Comando Grand, TH, 0.3 l/t and Cruizer 350 FS, 0.4 l/t were the most effective for the control of sucking phytophages of seedlings. The toxicity of winter wheat plants with insecticides under treatment contributed to higher qualitative and quantitative indicators of wheat yield as compared with a control variant. Under modern technologies of control, the growth and development intensity of sucking pests on winter wheat depends on climatic factors as well as on special protective measures on pests control on the first stages of crop organogenesis. The phytophageous insects spread and the harm under autumn control depend on timely monitoring when using the models of forecasting the number of sucking pests of the seedlings.